2007
DOI: 10.1080/10428190701395065
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation and hematopoietic-support of clonal cells in myelodysplastic syndromes

Abstract: Studies were performed to obtain evidence of the differentiating and hematopoietic potential of marrow clone-original cells in patients with myelodysplastic syndromes (MDS). First, results of correlation analysis between bone marrow clonal cells and blast percentages for a total of 60 MDS showed that almost all cases had higher clonal (mean 50.1%) than blast proportion (mean 7.0%) (p < 0.001). In contrast, in 16 AML patients, mean clone/blasts disparity was nearly zero. Secondly, the amount of clone-original i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…This phenomenon suggested that the majority of the clonal stem cells in MDS patients had somewhat retained their early differentiation potency but experienced difficulties in differentiating to more mature hematopoietic cells. Our results further verified our previous findings and those of other scholars regarding the blocked late differentiation of MDS clonal cells (16)(17)(18)(19). A few cases (7/46) showed that as the cells differentiated from stem cells to progenitor cells and then to advanced-stage hematopoietic cells, the clonal cell proportion increased.…”
Section: Discussionsupporting
confidence: 95%
“…This phenomenon suggested that the majority of the clonal stem cells in MDS patients had somewhat retained their early differentiation potency but experienced difficulties in differentiating to more mature hematopoietic cells. Our results further verified our previous findings and those of other scholars regarding the blocked late differentiation of MDS clonal cells (16)(17)(18)(19). A few cases (7/46) showed that as the cells differentiated from stem cells to progenitor cells and then to advanced-stage hematopoietic cells, the clonal cell proportion increased.…”
Section: Discussionsupporting
confidence: 95%
“…Among the nine MoAbs and immunoconjugates approved by FDA for therapeutic indications in oncological diseases, four have been approved for the treatment of haematological malignancies. Besides rituximab, which is currently tested for B-CLL patients, alemtuzumab, a recombinant DNA-derived humanized MoAb directed against the CD52 B-cell antigen, is approved for B-CLL patients not responding to fludarabine therapy; gemtuzumab ozogamicin, a MoAb conjugated with a cytotoxic antitumour antibiotic, is indicated for CD33 + relapsed AML in patients aged over 60; dozens more are in various stages of development [119][120][121].…”
Section: Rituximab Treatmentmentioning
confidence: 99%
“…Myelodysplastic syndromes (MDS) are clonal disorders of hematopoietic stem cells characterized by cytopenia with dysplastic phenotypes of myeloid cells [1], which have been thought to result from defective differentiation [2]. However, the molecular basis of impaired differentiation is largely unclear.…”
Section: To the Editormentioning
confidence: 99%